10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
BACKGROUND: Patient-reported outcome measures are increasingly used in mental health care, yet their acceptability and feasibility in tertiary settings, characterised by high acuity and clinical complexity, remain unclear. This review synthesised evidence on the implementation of patient-reported outcome measures in tertiary mental health services. METHODS: A systematic review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines (PROSPERO CRD420261290205). CINAHL, Cochrane Library, Ovid MEDLINE, and APA PsycINFO were searched for studies examining patient-reported outcome measure acceptability, feasibility, and implementation in tertiary mental health care. Study quality was appraised using the Mixed Methods Appraisal Tool, and findings were synthesised using narrative synthesis. RESULTS: Twelve studies from nine countries were included, with overall methodological quality ranging from moderate to high. Four interrelated themes were identified. Acceptability was highest when patient-reported outcome measures were used to support collaborative clinical dialogue, including co-designed approaches. Feasibility was determined by system integration and workflow alignment rather than patient-reported outcome measure characteristics. Implementation was shaped by patient capacity and clinician engagement, with implications for equity in participation. Sustainability depended on organisational governance, leadership, and resourcing. Across studies, patient-reported outcome measure use was primarily determined by relational, system, human, and organisational factors rather than by the measures themselves. CONCLUSION: Patient-reported outcome measures can be acceptable and feasible in tertiary mental health care when embedded within clinical practice and supported by integrated systems. Their value depends on implementation approaches that prioritise collaborative use, equity, and organisational support. These findings highlight the need to move beyond measurement-focused approaches towards multilevel implementation strategies in complex mental health settings.